Effect of Heat Treatment on High Temperature Damping Capacity of ZK60 Sheet Produced by Twin-roll Casting and hot-rolling - Chen Hongmei (Science Faculty of Chiang Mai University, 2019)
ZK60 alloy sheet with 1mm thickness which produced by twin roll casting and hot rolling was used in this paper. The effect of heat treatment on microstructure and damping capacity of the hot rolled ZK60 alloy sheet was studied by using optical microscope (OM) and dynamic mechanical analyzer (DMA). The microstructure of as rolled ZK60 alloy sheet was fibrous deformed structure with elongated grains, with a high density of shear bands along the rolling direction. The small and equiaxed recrystallized grains were obtained after annealing treatment, T4 and T6 treatment in hot rolled ZK60 alloy sheet. There is no P2 (around 280°C) damping peak in the hot rolled ZK60 alloy sheet. The damping peak P0 (around 50°C) was present in hot rolled ZK60 alloy sheet after annealing treatment. The damping peak P1 (around 150°C) was present in hot rolled ZK60 alloy sheet before and after heat treatment. The damping peaks P0 and P2 were not relaxation processes, but the damping peak P1 was relaxation processes. The activation energy for high temperature damping background (HTDB) after T6 treatment was higher than that after T4 treatment. The values of activation energy for high temperature damping background (HTDB) and damping peak P1 after annealing treatment was the lowest among different heat treatment.